United Nations role in resolution international conflicts - Suleymanov, A.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
In recent years ongoing international conflicts and border disputes intensified to an extent that certainly actualized a question of the role of the United Nations (UN) in the solution of these problems. Thereupon the objective of this article is to define the degree of influence of the United Nations and its precautionary effect on settlement of international conflicts at the present stage. The author makes the short analysis of intermediary activity of the United Nations and defines its legal basis. Besides, researcher considers the functionality specifics of the International Court of Justice (ICJ) of the United Nations and its actions aimed at the settlement of the territorial disputes and conflicts in the recent years. The basic method of this research is the comparative-historical approach which is used to reveal positive or negative dynamics of the United Nations performance at the present stage. Now the United Nations make active efforts in the solution of many international conflicts and lowering their escalation. However, despite of a growing demand for the solution of conflicts in a judicial order, the most serious problems of the international character remain insoluble. Nowadays the United Nations play a limited role in the settlement of the international problems. This is based on the fact that most parts of the conflicts evade UN resolutions which have only a recommendatory character. Therefore, the United Nations system needs certain reformation to reflect the new needs and realities in the world today. For the settlement of such challenging international conflicts it is necessary for all the countries to recognize jurisdiction of the UN ICJ.